2017
DOI: 10.1596/1813-9450-8162
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the Performance-Based Financing Black Box: Evidence from an Impact Evaluation in the Health Sector in Cameroon

Abstract: Performance-based financing is a complex health system intervention aimed at improving coverage and quality of care. This paper presents the results of an impact evaluation in Cameroon that seeks to isolate the role of specific components of the performance-based financing approach on outcomes of interest, such as explicit financial incentives linked to results, additional resources available at the point of service delivery (not linked to performance), and enhanced supervision, coaching, and monitoring. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 5 publications
4
31
1
Order By: Relevance
“…improve unrewarded dimensions of quality, including patient satis faction. 314,316,319 Overall, performance-based financing does not appear to be highly cost-effective, especially vis-à-vis unconditional additional financing. 316,317 The HCPPR showed that interventions that include financial incentives have a median increase on quality of 7•6 percentage points.…”
Section: The Lancet Global Health Commissionmentioning
confidence: 99%
See 2 more Smart Citations
“…improve unrewarded dimensions of quality, including patient satis faction. 314,316,319 Overall, performance-based financing does not appear to be highly cost-effective, especially vis-à-vis unconditional additional financing. 316,317 The HCPPR showed that interventions that include financial incentives have a median increase on quality of 7•6 percentage points.…”
Section: The Lancet Global Health Commissionmentioning
confidence: 99%
“…314,316,319 Overall, performance-based financing does not appear to be highly cost-effective, especially vis-à-vis unconditional additional financing. 316,317 The HCPPR showed that interventions that include financial incentives have a median increase on quality of 7•6 percentage points. For financial incentives, including performance-based financing programmes, to be successful, economic theory and research suggest that rewards will have smaller effects than penalties because of the tendency to avoid losses, and incentives are most effective when closely linked to processes under the direct control of providers.…”
Section: The Lancet Global Health Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] PBF, on the other hand, is generally a mechanism to measure and incentivize providers' and facilities' performance: facilities and providers earn incentives based on achievement of specific performance criteria. 21,28,29 For this review, we wanted to consider widely used approaches and platforms with potential to generate routine data for accountability on RMC in lower-resource settings. QI or assurance approaches have been used in LMICs for more than 30 years and are a major source of investment by major donors such as the United States Agency for International Development (USAID).…”
Section: Introductionmentioning
confidence: 99%
“…6 7 Evidence from PBF programmes across low-and middle-income countries is mixed in regard to its impact on service utilisation and quality. 8 9 PBF has been observed to yield a positive effect on maternal care services in Rwanda, 10 Burundi 11 and Tanzania, 12 but not in Afghanistan; 13 a positive effect on childhood immunisations in Cameroon 14 but not in Rwanda, 10 Afghanistan 13 or Burkina Faso; 15 and mixed effects on various indicators of quality of care. 9 Incentives have also been associated with drawbacks such as gaming by providers to maximise results 16 and perceptions of unfairness among providers in rewarding performance that negatively affects delivery of quality of care to clients.…”
Section: Introductionmentioning
confidence: 99%